Screening of congenital hypothyroidism in preterm, low birth weight and very low birth weight neonates: A systematic review - Mahin Hashemipour; Silva Hovsepian; Arman Ansari; Mojtaba Keikha; Pooyan Khalighinejad; Negar Niknam (Pediatrics and Neonatology)
Evidence from different screening programs indicated that the rate of congenital hypothyroidism (CH) was higher in pre-term and low-birth-weight (LBW) newborns than normal ones. Incomplete development of hypothalamic–pituitary axis in this group of neonates results in the delayed rise of TSH and missing cases with CH. Hence, there is a great need for a practicable systematic screening method for proper diagnosis of CH in this group of neonates. In this review, we systematically reviewed papers with the following key words ([Congenital Hypothyroidism AND Screening AND Thyroxine AND Thyroid Stimulating Hormone AND Low Birth Weight AND Premature]) in international electronic databases including PubMed, Scopus, and Google Scholar. After quality assessment of selected documents, data of finally included papers were extracted. In this review, 1452 papers (PubMed: 617; Scopus: 714; Google scholar: 121) were identified through electronic database search. One hundred and ninety four articles were assessed for eligibility, from which 36 qualified articles were selected for final evaluation. From the reviewed articles, 38.9%, 11.11% and 8.3% recommended rescreening in this group of neonates, lowering the screening cutoff of TSH and using cutoffs according to the gestational age, respectively. Some of them (13.9%) recommended using both TSH and T4 for screening of preterm infants. After reviewing available data, we recommend repeating the screening test in pre-term, LBW and very-low- birth-weight (VLBW) infants at age of two, six and ten weeks by measuring TSH and FT4 levels simultaneously and considering TSH = 10 mU/L as the cutoff level for positive and suspicious cases.